Histoire des idées : une certaine idée de l’histoire - Gérard Raulet (Recherches Germaniques)
The history of ideas is both courted and attacked by the philological sciences (history of philosophy, literary studies) and history as such. It appears as a kind of hybrid genus. In the light of its historical development, however, its key significance becomes evident. Anyone who classifies it as ‘foreign studies’, as practiced in foreign language teaching, forgets that it has arisen from the transformation of the chairs for foreign literatures, the general competence of which was modernized and specialized in the first decades of the 20th century. At that time, in the emerging German studies the history of ideas developed into a comprehensive discipline that united literary studies, culture and history. Even today it stands at the crossroads of several disciplines: the history of philosophy, the history of literature and culture, the history of mentalities and systems of knowledge. In order to play the resulting key role, however, it must reflect on its objects and its methods. Reflection on this reveals its specificity and its fruitfulness both in the research on past systems of knowledge (‘archives’) and in the intellectual and ideological debates of the present. At the point of contact between discourse analysis and the knowledge of reality, ‘discourse strategies’ prove to be its real area of competence. The present text develops this thesis through some significant examples.